STRATEGI PENGEMBANGAN AGRIBISNIS DAN AGROINDUSTRI SUB SEKTOR TANAMAN PANGAN DI KABUPATEN SITUBONDO - Djoko Soejono (University of Jember, 2011)
Development strategy research purposes agribusiness and agro food crops subsector in the district Situbondo are : (1) to determine the subsector agribusiness development centers crops , (2) to determine the trend of food commodities , (3) to analyze the value added of agro based food crops and (4) to strategize the development of agribusiness and agro food crop subsector in Situbondo. Research methods lead to the descriptive and analytical methods. The data used in this study is primary data and secondary data . Analysis tools to be used in the study are: (1) Location Quetion (LQ analysis ); (2) Trend Line Test with Total Least Squares Method, (3) value added analysis, and (4) FFA (Field Force Analysis). Discussion of results (1) Rice, maize, soybean, cassava , peanuts, green is a sector basis in some areas in Situbondo ,(2) types of food crops in 2010-2014 increased production are maize, cassava, peanuts, green beans, (3) agro based agricultural commodities community cultivated in Situbondo positive gain added value, and (4) alternative development strategy aimed at facilitating the establishment of agri terminal , which is supported by the activities of agroindustry incubator and cluster based agro commodities agriculture. Key Words : Agribusiness, agro-industry, food crops